Influência do ciclo de sinterização da porcelana na adaptação marginal de infraestruturas de NiCrTi em função da biomecânica do preparo - Almeida, Juliana Gomes Dos Santos Paes; Guedes, Carlos Gramani; Rached, Filipe de Oliveira Abi [UNESP]; Fonseca, Renata Garcia [UNESP] (My University, 2010)
A metal coping may undergo changes during porcelain firing, which compromises its marginal adaptation. The use of NiCrTi alloy proposes to minimize this effect through the high melting point of titanium present in its composition. This study evaluated the influence of porcelain firing cycle on the marginal adaptation of NiCrTi copings in different preparation designs. Forty standardized metal dies were fabricated with the following combinations finish line/convergence of the axial walls: 1) shoulder/6°; 2) shoulder/20°; 3) sloping shoulder/6°; 4) sloping shoulder/20°. On each die a metal ceramic restoration coping was made. The die/coping set was stabilized with orthodontic elastics, divided into four equidistant areas with three measurement points each and a cementation pressure was simulated. The measurements were taken under a stereomicroscope (32×). After the first measurement, the copings were submitted to sintering cycles simulating porcelain application. For repeated measurements, the same procedures described above were performed. Data were submitted to Student’s-t test, 1-way ANOVA and Tukey´s test (α = 0.05). Adaptation means (µm) before and after porcelain firing in different preparations were: 1) 111.92 and 127.31; 2) 124.15 and 135.48; 3) 122.19 and 138.77; 4) 166.09 and 186.72; respectively. The porcelain firing impaired adaptation, regardless of the preparation design. The preparation in a 20° sloping shoulder provided a worse adaptation when compared with preparations that had 6° and 20° shoulder, which were statistically equal. The 6° sloping shoulder was statistically equal to the other three preparation designs.

A infraestrutura metálica pode sofrer alterações durante a cocção da porcelana que comprometem sua adaptação marginal. A liga de NiCrTi propõe minimizar esse efeito por meio do alto ponto de fusão do titânio presente em sua composição. Este estudo avaliou a influência da temperatura de cocção da porcelana na adaptação marginal de infraestruturas de NiCrTi em diferentes formas de preparo. Foram confeccionados quarenta troquéis metálicos, com as seguintes combinações término cervical/expulsividade das paredes axiais: 1) ombro/6°; 2) ombro/20°; 3) plano inclinado/6°; 4) plano inclinado/20°. Sobre cada troquel, foi confeccionada uma infraestrutura para metalocerâmica. O conjunto troquel/infraestrutura foi estabilizado com elásticos ortodônticos, dividido em quatro faces equidistantes com três pontos de leitura cada e uma pressão de cimentação foi simulada. As leituras foram realizadas em estereomicroscópio (32×). Após a primeira leitura, as infraestruturas foram submetidas aos ciclos de aquecimento para sinterização da porcelana. Para a repetição das leituras, as mesmas condições descritas anteriormente foram realizadas. Os dados foram submetidos ao teste t-Student, ANOVA-1 fator e teste de Tukey (p < 0,05). As médias da fenda marginal (µm) antes e após a cocção da porcelana nos diferentes preparos foram, respectivamente: 1) 111,92 e 127,31; 2) 124,15 e 135,48; 3) 122,19 e 138,77; 4) 166,09 e 186,72. A cocção da porcelana prejudicou a adaptação, independentemente da forma do preparo. O preparo em plano inclinado 20° promoveu uma pior adaptação quando comparado aos preparos em ombro 6° e 20°, que foram estatisticamente iguais entre si. O preparo em plano inclinado 6° foi estatisticamente igual às outras três formas de preparo.
Influence of porcelain firing cycles on marginal adaptation of NiCrTi copings depending on the preparation biomechanics
Keywords: Marginal adaptation; Metal ceramic alloys; Tooth preparation; Adaptação marginal; Ligas metalocerâmicas; Preparo dental